Effectiveness of Group Discussion Method to Improve 21st Century Learning Skills of Elementary School Students - Jihan Deana Safitri; Yosi Gumala (Penerbit Hellow Pustaka, 2025)
This study explores the effectiveness of group discussion methods in enhancing students' learning outcomes, critical thinking skills, and communication abilities across various educational levels. Through group discussions, students engage directly with classmates, not only improving material comprehension but also developing collaboration skills and an appreciation for diverse perspectives. The findings show that this method positively impacts students' understanding, both in social and exact sciences. The success of group discussion largely depends on active student involvement and teachers’ facilitation skills. Although effective, implementing this method requires careful planning and an active teacher role to address challenges such as unequal student participation and the need for relevant material preparation. By overcoming these challenges, group discussions can become a learning approach that deeply engages students while building critical and collaborative skills essential for their future.